CD38-directed CAR-T cell therapy: a novel immunotherapy strategy for relapsed acute myeloid leukemia after allogeneic hematopoietic stem cell transplantation - Qingya Cui; Chongsheng Qian; Nan Xu; Liqing Kang; Haiping Dai; Wei Cui; Baoquan Song; Jia Yin; Zheng Li; Xiaming Zhu; Changju Qu; Tianhui Liu; et al. (Journal of Hematology & Oncology, 2021)
Abstract Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potentially curative treatment for acute myeloid leukemia (AML). However, most patients experience relapse after allo-HSCT, with a poor prognosis, and treatment options are limited. The lack of an ideal targetable antigen is a major obstacle for treating patients with relapsed AML. CD38 is known to be expressed on most AML and myeloma cells, and its lack of expression on hematopoietic stem cells (HSCs) renders it a potential therapeutic target for relapsed AML. To investigate the clinical therapeutic efficacy and safety of CD38-targeted chimeric antigen receptor T (CAR-T-38) cells, we enrolled 6 AML patients who experienced relapse post-allo-HSCT (clinicaltrials.gov: NCT04351022). Prior to CAR-T-38 treatment, the blasts in the bone marrow of these patients exhibited a median of 95% (92–99%) CD38 positivity. Four weeks after the initial infusion of CAR-T-38 cells, four of six (66.7%) patients achieved complete remission (CR) or CR with incomplete count recovery (CRi); the median CR or CRi time was 191 (range 117–261) days. The cumulative relapse rate at 6 months was 50%. The median overall survival (OS) and leukemia-free survival (LFS) times were 7.9 and 6.4 months, respectively. One case relapsed 117 days after the first CAR-T-38 cell infusion, with remission achieved after the second CAR-T-38 cell infusion. All six patients experienced clinically manageable side effects. In addition, multiparameter flow cytometry (FCM) revealed that CAR-T-38 cells eliminated CD38 positive blasts without off-target effects on monocytes and lymphocytes. Although this prospective study has a limited number of cases and a relatively short follow-up time, our preliminary data highlight the clinical utility and safety of CAR-T-38 cell therapy in treating relapsed AML post-allo-HSCT.